2012
DOI: 10.1029/2012gl051570
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability and a recent amplification of the summer Beaufort Sea High

Abstract: [1] The Beaufort Sea High (BSH), an anti-cyclone over the Beaufort Sea, is an important feature of the summer atmospheric circulation over the Arctic Ocean. For example, years characterized by low Arctic sea ice extent are typically associated with the presence of a stronger BSH; with the opposite occurring during years with high sea ice extent. In this paper, we show that there exists variability on the decadal time scale in the intensity and location of the summer BSH. We also show that there has been a tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 29 publications
3
53
0
Order By: Relevance
“…A strengthening of the Beaufort High during summer has been documented [72] along with stronger onshore winds in northern Alaska [73]. The reduced slp over Eurasia is consistent with the strengthening of the positive phase of the Arctic Rapid change Pattern (ARP) that links sea-ice loss to enhanced poleward heat and moisture transport induced by recent shifts in this circulation pattern [74].…”
Section: Consequences Of Large-scale and Long-term Climate Variabilitmentioning
confidence: 69%
“…A strengthening of the Beaufort High during summer has been documented [72] along with stronger onshore winds in northern Alaska [73]. The reduced slp over Eurasia is consistent with the strengthening of the positive phase of the Arctic Rapid change Pattern (ARP) that links sea-ice loss to enhanced poleward heat and moisture transport induced by recent shifts in this circulation pattern [74].…”
Section: Consequences Of Large-scale and Long-term Climate Variabilitmentioning
confidence: 69%
“…Recent boreal summers have also been characterized by a changing Arctic atmospheric circulation, with increased anticyclonic flow over the Arctic (Ogi and Wallace 2012) and a more persistent negative Arctic Dipole (Overland et al 2012) associated with increased Greenland blocking and a strengthened Beaufort Sea high pressure region (Moore 2012;Wu et al 2014;Ballinger et al 2014). These have resulted in a southward displacement of the PFJ, leading to cooler wetter summers in Europe, while other areas such as North America have experienced heatwaves and droughts.…”
Section: Introductionmentioning
confidence: 99%
“…The signature of the sum-mer BH is also quite variable from year to year. Using the global NCEP reanalysis fields, Moore (2012) analyzed the signature of the summer (June, July, August) BH from 1948 to the present and found that, while there is a great deal of interannual variability, for most of the record there were no noticeable trends. However, since the mid-1990s a statistically significant positive trend has occurred in the strength of the summer BH.…”
Section: Interannual Variability Of the Circulationmentioning
confidence: 99%
“…Interestingly, there has been an increase in the 13 strength of the summertime Beaufort High in the last decade, (Moore, 2012), while there is still debate as to the interannual variability of the Aleutian Low (McCabe et al, 2001;Mesquita et al, 2010).…”
mentioning
confidence: 99%